Assistência à saúde mental do idoso em Unidades de Atendimento de Passo Fundo - Lopes, Bruna Chaves (2012)
The issue of health and care provided by professionals with regard to mental health of the elderly has been discussed in its various aspects, passing through several areas of knowledge. It is observed that since the concept of health and sub-sector of mental health has been modified in an attempt to adapt practices to changing times. When you talk about the mental health of the elderly, is added characteristics of a population with specific demands and poorly determined by its complexity. Given this reality, the study aimed to examine the training of health workers on mental health of the elderly. This is an exploratory descriptive study with qualitative approach. Study participants were professionals working in primary health and specialist mental health center of Passo Fundo, totaling sixteen participants. It was applied an interview and performed thematic analysis of discourse. The data obtained indicate that there is a deficiency in the training of professionals working in the service network, affecting the quality of care for this population. The elderly have unique characteristics that demand another look in assisting, supporting the need for the elaboration of public policies that address regional aspects of individual, social and cultural needs of patients and professionals working in the area. The issue of education and training seem to indicate a possible path, indicating the need to implement strategies focused on these aspects